If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 30) = 0 Reorder the terms: 2(30 + x) = 0 (30 * 2 + x * 2) = 0 (60 + 2x) = 0 Solving 60 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + 2x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + 2x = 0 + -60 2x = 0 + -60 Combine like terms: 0 + -60 = -60 2x = -60 Divide each side by '2'. x = -30 Simplifying x = -30
| 6n-2=14 | | 52=(3x+6)+(6x+22) | | 3(5+x)=31+x | | 51=(2+7x)+(20x+1) | | 50=(8x-6)+(13x+9) | | 87=(8x+2)+(8x+5) | | x-9= | | 8n+8=16 | | 95=(3+8x)+(14x+4) | | 8n+2=16 | | 8n+6=16 | | 8n+6=24 | | 3x+2=7.5 | | 9x+7y=10 | | 57=(9x-2)+(23x-1) | | x+2(x+1)=35 | | 54=(17x+3)+(25x+9) | | 20=(8x+4)+(9x+12) | | 10v+7=8(2u-4)-9 | | 6x+2=8x+14 | | 4(x+1)=8 | | 2p-1=-4p-19 | | (2y-5)-8+y=5 | | 80=(x+9)+(6x-6) | | x^2-42xy-343y^2=0 | | 48=(14x+4)+(24x+2) | | 2b^2+7b=15 | | 2(4p+8)=128 | | x^2+3x-7=0 | | x^2-98=0 | | 2x^2-13x-7=0 | | 4(n+1)+2n=22 |